Paying it forward: A cancer survivor and his wife share their reflections and recommendations as a patient and caregiver - Justin Sandler (The Beryl Institute, 2020)
I grew up in the north suburbs of Chicago and had a relatively normal childhood but not necessarily an easy one. Shortly after graduating from Indiana University, I moved out west and have been working in the entertainment industry ever since. My life has been a beautiful and interesting adventure with twists and turns I could have never predicted. In 2016 it seemed like everything was really coming together. I had been happily married to my wife and business partner Mary Lou Sandler since 2011, and we had been growing our photography/film production studio for as many years. I was in peak physical condition. I felt good. I thought I was ready for the next level in life. In fact, I was declaring it. I was ready! It was of great surprise to us all when on May 4, 2017 I was diagnosed with cancer in the form of a large germ cell tumor, located inside of my chest and aggressively growing into my heart and lung. It’s very easy to fall into the victim role. After being diagnosed, I made a firm decision to instead be the victor... it changed everything. Through a philosophy I call “Embrace Love Free," I began to view cancer in an entirely new way. With the experience of facing an illness, one can grow and evolve in unimaginable ways. When it comes to my caregiver Mary Lou, it’s a similar yet very different story. While we both were on this journey together, I had to drop everything to focus on survival. She had to drop everything to care for me. It is from our own positive experience that we want to see medical professionals improve the experience of cancer patients by incorporating things like meditation, aromatherapy, positive thinking, and healthier food choices.